Analysis and Modelling of Ultrasonic Pulses in a Biological Medium - OPIELIŃSKI, Krzysztof J. (Archives of Acoustics, 2008)
In this work, formulas were presented, which allow modelling of linear and nonlinear propagation of ultrasonic wave in a biological medium, by simulating the shape of pulses which propagate in this medium. Analysed and measured in chosen biological media using transmission method, the linear and nonlinear ultrasonic pulses were modelled by means of developed formulas. Very good compatibility of the representation was achieved both in the area of time and frequency. In case of biological media causing high attenuation of ultrasonic wave, reduction of mid frequency in the receiving pulse caused by attenuation dispersion was observed.